Application of Transit Oriented Development (TOD)Concept in Gelora Bung Karno Area - Taki, Herika Muhamad (Universitas Negeri Semarang, 2024)
In the present era, many individuals rely on public transportation to meet their daily needs, particularly in Jakarta, Indonesia. Various options, such as trains and buses, serve as the primary choices for public transportation. This study, which focuses on the Gelora Bung Karno Stadium (GBK) area, explores the implementation of the Transit Oriented Development (TOD) concept. TOD is a planning strategy that aims to create compact, mixed-use communities centered around transit stations, with the intention to enhance economic growth, facilitate access to integrated public transportation, and reduce reliance on private vehicles to mitigate air pollution levels in the city. The research findings indicate that applying this concept can positively impact economic development and the efficiency of public transportation while concurrently fostering a cleaner and more sustainable environment for urban communities. This study is pertinent to current dynamics, where an increasing number of individuals are opting for public transportation as a primary solution to address urban mobility challenges.